2009
DOI: 10.1111/j.1365-2133.2009.09046.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in theP2RY5gene underlie autosomal recessive hypotrichosis in 13 Pakistani families

Abstract: Mutations revealed in the present study extend the body of evidence implicating the P2RY5 gene in the pathogenesis of human hereditary hair loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 16 publications
(56 reference statements)
0
23
0
Order By: Relevance
“…The autosomal recessive forms of hair loss disorders have been shown to result from mutations in hairless (HR, MIM 225060) Cichon et al 1998), desmoglein 4 (DSG4, MIM 607892) (Kljuic et al 2003), lipase-H (LIPH, MIM 607365) (Kazantseva et al 2006;Ali et al 2007), G-protein coupled receptor (P2RY5, MIM 609239) (Shimomura et al 2008;Pasternack et al 2008;Azeem et al 2008;Tariq et al 2009) and desmocollin-3 (DSC3, MIM 600271) ) genes. The genes for the three recently reported autosomal recessive forms of hair loss disorders (Naz et al 2010;Basit et al 2010a, b) have not been identified to date.…”
Section: Introductionmentioning
confidence: 99%
“…The autosomal recessive forms of hair loss disorders have been shown to result from mutations in hairless (HR, MIM 225060) Cichon et al 1998), desmoglein 4 (DSG4, MIM 607892) (Kljuic et al 2003), lipase-H (LIPH, MIM 607365) (Kazantseva et al 2006;Ali et al 2007), G-protein coupled receptor (P2RY5, MIM 609239) (Shimomura et al 2008;Pasternack et al 2008;Azeem et al 2008;Tariq et al 2009) and desmocollin-3 (DSC3, MIM 600271) ) genes. The genes for the three recently reported autosomal recessive forms of hair loss disorders (Naz et al 2010;Basit et al 2010a, b) have not been identified to date.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, several mutations in the P2RY5 gene encoding G-protein-coupled receptor (P2Y5) has been reported to cause autosomal recessive hypotrichosis (Pasternack et al 2008;Azeem et al 2008;Tariq et al 2009). The P2Y5 was recently deciphered as key regulator of the hair follicle development.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these four autosomal dominant forms of hereditary hypotrichosis, six isolated autosomal recessive forms have been mapped on diVerent human chromosomes. Congenital atrichia (MIM 203655), characterized by complete absence of scalp and body hair and appearance of papules mostly on scalp, has been reported to result from mutations in hairless (HR, MIM 225060) Cichon et al 1998) gene mapped on chromosome 8p21 Nothen et al 1998 (Aslam et al 2004) and LAH3 (MIM 611452) on 13q14.11-q21.32 (Wali et al 2007b) have been shown to result from the mutations in desmoglein 4 (DSG4, MIM 607892) (Kljuic et al 2003;RaWq et al 2004), lipase-H (LIPH, MIM 607365) (Kazantseva et al 2006;Ali et al 2007) and G-protein-coupled receptor (P2RY5, MIM 609239) gene (Pasternack et al 2008;Shimomura et al 2008;Azeem et al 2008;Tariq et al 2009), respectively. Patients with these three forms of localized hereditary hypotrichosis show either complete absence or wooly hair on scalp, sparse eyebrows and eyelashes, and sparse to absent body hair (Wali et al 2007b;Pasternack et al 2008;Shimomura et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The isolated hair loss disorders with variable clinical features, segregate either in autosomal dominant or recessive pattern [9]. Over the past few years, five genes including hairless (HR, MIM 225060) [2,11], desmoglein-4 (DSG4, MIM 607892) [25,43], lipase-H (LIPH, MIM 607365) [4,22,30], lysophosphatidic acid receptor 6 (LPAR6/P2RY5, MIM 609239) [7,34,36,39,42], and desmocollin-3 (DSC3, MIM 600271) [6] associated with the isolated (non-syndromic) forms of hair loss disorders have been characterized. In syndromic form of hair loss disorders, hair loss is associated with other abnormalities including impaired sweating, nail dystrophy, deformed or absent teeth, mental retardation, etc.…”
Section: Introductionmentioning
confidence: 99%